Umbilical cord milking and delayed cord clamping for the prevention of neonatal hypoglycaemia: a systematic review and meta-analysis - Estelle D. Watson; Lily F Roberts; Jane E Harding; Caroline A Crowther; Luling Lin (BMC, 2024)
Abstract Background Placental management strategies such as umbilical cord milking and delayed cord clamping may provide a range of benefits for the newborn. The aim of this review was to assess the effectiveness of umbilical cord milking and delayed cord clamping for the prevention of neonatal hypoglycaemia. Methods Three databases and five clinical trial registries were systematically reviewed to identify randomised controlled trials comparing umbilical cord milking or delayed cord clamping with control in term and preterm infants. The primary outcome was neonatal hypoglycaemia (study defined). Two independent reviewers conducted screening, data extraction and quality assessment. Quality of the included studies was assessed using the Cochrane Risk of Bias tool (RoB-2). Certainty of evidence was assessed using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach. Meta-analysis using a random effect model was done using Review Manager 5.4. The review was registered prospectively on PROSPERO (CRD42022356553). Results Data from 71 studies and 14 268 infants were included in this review; 22 (2 537 infants) compared umbilical cord milking with control, and 50 studies (11 731 infants) compared delayed with early cord clamping. For umbilical cord milking there were no data on neonatal hypoglycaemia, and no differences between groups for any of the secondary outcomes. We found no evidence that delayed cord clamping reduced the incidence of hypoglycaemia (6 studies, 444 infants, RR = 0.87, CI: 0.58 to 1.30, p = 0.49, I2 = 0%). Delayed cord clamping was associated with a 27% reduction in neonatal mortality (15 studies, 3 041 infants, RR = 0.73, CI: 0.55 to 0.98, p = 0.03, I2 = 0%). We found no evidence for the effect of delayed cord clamping for any of the other outcomes. The certainty of evidence was low for all outcomes. Conclusion We found no data for the effectiveness of umbilical cord milking on neonatal hypoglycaemia, and no evidence that delayed cord clamping reduced the incidence of hypoglycaemia, but the certainty of the evidence was low.